2010
DOI: 10.1590/s1415-47572010000300018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reference genes for real-time PCR studies of Brazilian Somalis sheep infected by gastrointestinal nematodes

Abstract: Precise normalization with reference genes is necessary, in order to obtain reliable relative expression data in response to gastrointestinal nematode infection. By using sheep from temperate regions as models, three reference genes, viz., ribosomal protein LO (RPLO), glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and succinate dehydrogenase complex subunit A (SDHA), were investigated in the abomasum, abomasal lymph nodes and small intestine of Brazilian Somalis sheep, either resistant or susceptible to gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
3
17
0
2
Order By: Relevance
“…Other studies have assessed the stability of various genes frequently used in qRT-PCR in sheep 16,17,28,29 . Only one of these studies identified one of our selected reference genes (PGK1) as suitable for accurate and reproducible qRT-PCR analysis of gene expression in sheep.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have assessed the stability of various genes frequently used in qRT-PCR in sheep 16,17,28,29 . Only one of these studies identified one of our selected reference genes (PGK1) as suitable for accurate and reproducible qRT-PCR analysis of gene expression in sheep.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some studies have been published focusing on the identification and selection of sheep reference genes in abomasum, skin and leukocyte cells 16–18 . To the best of our knowledge, no study has addressed the selection of suitable reference genes for F. hepatica in liver and lymph nodes tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal nematode infection is the most worrisome disease for producers of cattle, sheep, and goats because they cause major losses, reducing economic return due to death of the animals and negative effects on the performance of the herd (Zaros et al, 2010a;Bishop, 2012;Silva et al, 2012). The susceptibility to nematode infections seems to be related to genetic factors, and resistance may vary among breeds (Pralomkarn et al, 1997;Baker, 1998;Mandonnet et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Nesse método o valor da eficiência é determinado a partir da inclinação da curva padrão (CIKOS et al, 2007;RASMUSSEN et al, 2001). Um método alternativo foi desenvolvido por Ramakers et al (2003 (MCCURLEY et al, 2008;PÉREZ et al, 2008;ZAROS et al, 2010), o que torna a seleção do gene referência uma tarefa trabalhosa.…”
Section: Rt-pcr Quantitativa Em Tempo Realunclassified
“…Diversos autores (BUSTIN et al, 2005;VANDESOMPELE et al,2009;CIKOS et al, 2008, ZAROS et al, 2010 relataram que a utilização de um único gene referência para a normalização não é aceitável e recomendam o uso de múltiplos genes referência como fator de normalização. Nesse sentido, em busca da correta análise dos dados de expressão gênica, foram utilizadas duas abordagens de normalização.…”
Section: Normalização E Análise Dos Dadosunclassified